Ultrafiltration: Purification of PEDOT:PSS by Ultrafiltration for Highly Conductive Transparent Electrode of All‐Printed Organic Devices (Adv. Mater. 46/2016). Issue 46 (December 2016) - Kim, Soyeon; Sanyoto, Bernardi; Park, Won‐Tae; Kim, Seyul; Mandal, Saumen; Lim, Jong‐Choo; Noh, Yong‐Young; Kim, Jung‐Hyun
Abstract : On page 10149, a simple and mass‐scalable method, ultrafiltration, is proposed for achieving high‐conductivity poly(3, 4‐ethylenedioxythiophene) (PEDOT): poly(4‐styrenesulfonate) (PEDOT:PSS) by Y.‐Y. Noh, J.‐H. Kim, and co‐workers. By effectively removing excess PSS and various reaction impurities using repeated 100 nm‐poremembrane filtration, the purified PEDOT:PSS shows impressive conductivity and sheet resistance as high as 2000 S cm −1 and 37.8 ± 4.5 Ω□ −1, respectively.